The physical design of on-chip interconnections. - Wisniewski, M.Y.L (IEEE Transactions on computer-aided design of integrated circuits and systems)
Because of the complexity of the route problem in ultra large scale integrated (ULSI) designs, multiple route solutions are possible, some route solutions are more efficient than others, and there is a need for statistical tools to determine whether a designer or preroute algorithm is following an efficient path. In a ULSI environment, the problem of routing is best addressed with the combination of a customized preroute algorithm and routing system. One of the key issues in this context is how to divide the routing task between the preroute algorithm and the routing system; to address this issue, it is necessary to develop criteria to assign certain signals to the preroute algorithm and other signals to the routing system. Another key issue is how to evaluate the interactions of the combination of the algorithm and the routing system in order to decide whether intervention with the preroute algorithm is effective in improving physical properties of routes for select signals without adversely affecting physical properties of routes generated with the routing system. In a practical implementation, it is also important to predict when the combined effort is likely to improve the existing solution and to establish a point of diminishing returns beyond which further interactions are no longer effective. This paper presents a self-consistent formalism for intervention with preroute algorithms in ULSI designs. A framework is presented to quantify the physical properties of routes prepared with a preroute algorithm. This paper also presents statistical frameworks to assess the effectiveness of a preroute algorithm and to decide when to stop its use. The main emphasis is on incorporating intervention with custom algorithms in the design process in a seamless manner. The frameworks presented in this paper are applied to an analysis of the POWER4 Instruction Fetch Unit; in this example, the preroute algorithm is custom interconnection design.